The Relationship between Retinol-Binding Protein 4 and Markers of Inflammation and Thrombogenesis in Children with Kawasaki Disease - Maoling Yang; Haobo Weng; Qiongfei Pei; Fengchuan Jing; Qijian Yi (Mediators of Inflammation)
Background. Kawasaki disease (KD) is a self-limited vasculitis with unknown etiologies, and coronary artery lesions (CALs) are the most common and serious complications. Retinol-binding protein 4 (RBP4) has been confirmed effects on vasodilation, platelet activation inhibition, and cardiovascular diseases by researches. Therefore, this study was aimed at investigating the relationship between RBP4 and inflammation as well as thrombogenesis in children with KD. Methods. 79 subjects were from 62 children with KD and 17 healthy controls (HCs). The KD group was divided into KD with CALs (KD-CALs) and KD without CALs (KD-NCALs), and the serum RBP4 levels were measured by enzyme-linked immunosorbent assay (ELISA). Results. Compared with the HC group, serum RBP4 levels in the KD group were significantly decreased (p<0.05). RBP4, hemoglobin (Hb), and mean platelet volume (MPV) levels were higher, while platelet counts (Plt) and thrombin time (TT) levels were lower in the KD-NCALs group than in the KD-CALs group (p<0.05). RBP4 had positive correlation with time point of intravenous immunoglobulin (IVIG), Hb, and percentage of leukomonocytes (L%) and negative correlation with the percentage of neutrophils (N%), MPV, C-reactive protein (CRP), neutrophil-to-lymphocyte ratio (NLR), prothrombin time (PT), fibrinogen (Fbg), and D-dimer (DD) in the KD group; RBP4 had positive correlation with the time point of IVIG and L% and negative correlation with N%, MPV, and NLR in the KD-NCALs group; and RBP4 had positive correlation with Hb and L% and negative correlation with N%, CRP, NLR, and PT in the KD-CALs group (p<0.05). Multiple linear regression analysis confirmed that Hb and CRP in the KD group, MPV and N% in the KD-NCALs group, and PT and CRP in the KD-CALs group were independent predictors of RBP4 (p<0.05). Conclusion. Lower RBP4 was observed in the KD group than in the HC group, and RBP4 had associations with markers of inflammation and thrombogenesis in children with KD.